2009
DOI: 10.3109/08830180903208329
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Immune Regulation as a Potential Diet-Modifiable Feature of Gut Inflammation and Autoimmunity

Abstract: The gastrointestinal tract represents the largest immune interface with the environment. Exposure to large numbers of dietary and microbial antigens requires complex and highly regulated intestinal immune responses by different immune cell types for the maintenance of oral tolerance. Defective immune homeostasis can cause gut barrier dysfunction and breakdown of tolerance, leading to chronic inflammation and autoimmunity. In this review, we summarize the key immune cell populations involved in oral tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 201 publications
0
24
0
Order By: Relevance
“…These comprise autoimmune diseases, including T1D (107,117,149,163), CD (45,46,51,126), multiple sclerosis (124,176,184), and rheumatoid arthritis (52), in which intestinal TJs allow the passage of antigens from the intestinal milieau, challenging the immune system to produce an immune response that can target any organ or tissue in genetically predisposed individuals (1,13,57,58,70,151). TJs are also involved in cancer development, infections, and allergies (32,55,57,147).…”
Section: Intestinal Permeability and Diseasementioning
confidence: 99%
“…These comprise autoimmune diseases, including T1D (107,117,149,163), CD (45,46,51,126), multiple sclerosis (124,176,184), and rheumatoid arthritis (52), in which intestinal TJs allow the passage of antigens from the intestinal milieau, challenging the immune system to produce an immune response that can target any organ or tissue in genetically predisposed individuals (1,13,57,58,70,151). TJs are also involved in cancer development, infections, and allergies (32,55,57,147).…”
Section: Intestinal Permeability and Diseasementioning
confidence: 99%
“…Increased zonulin concentrations are related to changes in tight junction competency and increased GI permeability [21]. The “leak” in the paracellular absorption route enables antigens to pass from the intestinal milieau, challenging the immune system to produce an immune response and subsequent inflammation and oxidative stress [13,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Impact of environmental stress and infections caused by pathogens could lead to dysfunctional epithelium; furthermore, chronic inflammatory disorders (e.g. Crohn’s disease and ulcerative colitis) and other kind of diseases could be developed such as type 1 diabetes [1,2,3]. Many studies have shown that the chronic phase of inflammation is clearly associated with the up-regulation of certain enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%